Manifatture fittili nella ApVlia et Calabria - Silvio Fioriello, Custode; Mangiatordi, Anna (Rei Cretariae Romanae Fautorum Acta, 2022)
The archaeological investigations conducted in Apulia et Calabria provide a picture of the settlement and socio-economic history of the region for the Roman period: however there has been no contextual study of either the production installations, primarily for pottery, or on the related processes of manufacture, trade and consumption. So we present the preliminary results of the research just begun that aims to identify the spaces designated for pottery and tile production in the named territory between the 3rd century BC and the 3rd century AD. Useful indicators were both permanent installations (kilns, etc.) and portable artefacts (tools, waste products). The data collected allow us to identify numerous contexts: 36 active between the end of the 4th and the 2nd century BC, 43 between the 2nd and the 1st century BC (18 of which were still functioning in the early Imperial age), 14 between the 1st and the beginning of the 4th century AD (one only continuing until the 6th century), 16 generically attributable to the Roman period. This study does not include the early phase of Romanisation, with attendant issues concerning continuity and discontinuity, but spans the period from the bellum sociale to the beginning of the 4th century AD. The catalogue takes into account both specific previous studies and consolidated methodological approaches which propose a ‘global’ analysis of Roman craftsmanship in an overall Mediterranean view, from the examination of material culture to the dynamics of the circulation of goods.